4-1BB Agonism Combined With PD-L1 Blockade Increases the Number of Tissue-Resident CD8+ T Cells and Facilitates Tumor Abrogation - Qu, Qiu-xia; Zhu, Xin-yun; Du, Wen-wen; Wang, Hong-bin; Shen, Yu; Zhu, Yi-bei; Chen, Cheng (Frontiers in Immunology, 2020)
Although the milestone discovery of immune checkpoint blockade (ICB) has been translated into clinical practice, only a fraction of patients can benefit from it with durable responses and subsequent long-term survival. Here, we tested the anti-tumor effect of combining PD-L1 blockade with 4-1BB costimulation in 3LL and 4T1.2 murine tumor models. Dual treatment induced further tumor regression and enhanced survival in tumor-bearing mice more so than PD-L1 and 4-1BB mAb alone. It was demonstrated that dual anti-PD-L1/anti-4-1BB immunotherapy increased the number of intratumoral CD103+CD8+ T cells and altered their distribution. Phenotypically, CD103+CD8+ T cells expressed a higher level of 4-1BB and PD-1 than their CD103− counterparts. Administration of PD-L1 mAb and 4-1BB mAb further increased the cytolytic capacity of CD103+CD8+ T cells. In vivo, CD103−CD8+ T cells could differentiate into CD103+CD8+ progeny cells. In a human setting, more CD8+ T cells differentiated into CD103+CD8+ T cells in the peripheral tumor region of lung cancer tissues than in the central tumor region. Collectively, infiltrated CD103+CD8+ T cells served as a potential effector T cell population. Combining 4-1BB agonism with PD-L1 blockade could increase tumor-infiltrated CD103+CD8+T cells, thereby facilitating tumor regression.